Accuracy of dental microwear impressions by physical properties of silicone materials - Sawaura, Ryohei; Kimura, Yuri; Kubo, Mugino O. (Frontiers in Ecology and Evolution, 2022)
In dental microwear analysis, the impression molds or resin casts are often analyzed rather than the original tooth surfaces. A choice of silicone products for dental impression is crucial because the quality of microwear data is affected by the impression accuracy of the molds. For this reason, microwear researchers have heavily depended on a few commercial products such as “President” (Coltène/Whaledent AG, Switzerland) to avoid analytical errors caused by using different silicone materials. Considering that the production business might be terminated, however, heavy reliance on specific products could be a potential weakness in the field. In this study, we aim at identifying specific indexes on physical properties of silicone materials to find appropriate silicones that mold the tooth surface with satisfactory accuracy as does the standard product of microwear research. For this purpose, we measured dynamic viscoelasticity and shrinkage rates of various silicone compounds including the standard impression material President and other eight affordable dental silicones. Furthermore, to investigate the accuracy of silicone molds, we scanned both original tooth surface and dental impression molds with a confocal laser microscope, and conducted dental microwear texture analysis (DMTA) to quantitatively compare the scanned surfaces. The results showed relationships between material properties of silicones and impression accuracy, indicating that the materials that cured slowly and began to shrink relatively early in the hardening process were less accurate. Some of these dental impression molds showed blurred surfaces, implying that molds were peeled off from the tooth surface at the microscopic level, as the shrinkage speed might exceed the curing speed. Among the tested materials, President regular and Dr. Silicon regular had equally high accuracy. The following indexes provided in the product information were found to be helpful in the search for substitutes: 1) medium viscosity, 2) short curing time after mixing (5-6 minutes).